Analisis Pengaruh Model Manajemen Kinerja Dosen terhadap Prestasi Taruna Akademi Maritim Belawan Medan - Saragih, Veronika; Sagala, Ade Irma (Majalah Ilmiah Gema Maritim, 2024)
The lecturer's performance management model in carrying out their duties must have a well-planned understanding of the teaching and learning process. Lecturers establish strategies, methods, and media to implement effective learning processes, thus enabling learning objectives to be achieved. The purpose of this research is to examine the influence of the lecturer performance management model in improving cadet achievement. The research is quantitative. The research subjects are lecturers and cadets. The sample set consists of 30 cadets selected using the Accidental Sampling method. The data collection technique is done through questionnaires. The results obtained from the research indicate that the lecturer performance management model influences cadet learning achievement, there is a relationship between lecturer performance management and cadet learning outcomes at the Maritime Academy Belawan Medan.